Girl in a band - Gordon, Kim 1953- (Dey Street Books, 2015)
A founding member of Sonic Youth, fashion icon, and role model for a generation of women, now tells her story -- a memoir of life as an artist, of music, marriage, motherhood, independence, and as one of the first women of rock and roll
Keywords: Gordon, Kim / 1953-; Moore, Thurston; Gordon, Kim -- 1953-; Sonic Youth (Musical group); Sonic Youth -- Musikgruppe; Geschichte 1953-; Alternative rock musicians / United States / Biography; Rock musicians / United States / Biography; Women singers / United States / Biography; Singers / United States / Biography; Guitarists / United States / Biography; Rockmusikerin; USA; Biografie